Cooks Training for Faith, Activity, and Nutrition project with AME churches in SC - Condrasky, Margaret D. (2012)
PURPOSE: This study describes the development and evaluation of a participatory training for cooks in African American churches. The 8-hour training focused on providing healthy meals within the church food program. It enlisted cooks in hands-on “cooking with the chef” training and menu building exercises, and demonstrated development of flavor in foods through healthy ingredients. Cook ratings from pre- to post-training (possible range: 1 to 10) were evaluated with the Wilcoxon signed rank test. RESULTS: 114 cooks from 57 churches over the period from 7/21/07 to 3/21/11 participated in trainings. Self-rated cooking skill increased from pre- (6.5 ± SD) to post- training (7.9 ± SD), p = .0001. Self-rated confidence in preparing meals also increased significantly (pre: 7.3 ± SD; post: 8.3 ± SD), p =.0001. Qualitative feedback from the cooks’ training has been positive. Two of the more frequently stated changes cooks report are using less salt and using more vegetables and fruits in menus. Lessons learned include: choosing the right church to host the training, teamwork as a key component, need for support system for church cooks, allocation of time for planning as well as shopping for healthy ingredients, and incorporation of flexibility into the training plan.